Belajar Islam Itu Penting: Studi Deskriptif-Komparatif Kesejahteraan Spiritual Antara Pemuda yang Melihat Kajian Secara Daring dan Yang Melihat Kajian Islam Secara Tatap Muka - Yundianto, Devie; Khatami, Muhammad; Fikri, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
The digital age is an era that facilitates human in many ways, including learning in Islam. The ease in getting internet access and great curiosity in Islamic teaching make the community, especially young people can get qualified Islamic Lecturer (Ustadz) lectures in just one click, like Youtube (online). On the other hand, there are some experts who say that in Islamic Learning, individual should immediately come face to face in attending the lecture and have a lot of friends to motivate the learning (offline). Islamic learning has been viewed as a tools in rasing the faith to God (Allah); in the deity that cannot be seen, in which the spiritual well being is the one of helping indicators in comprehending life. Spiritual well-being is a variable of social psychology and positive psychology that supports a person in understanding the meaning of life and one's belief in a power greater than oneself. Some literature reveals some discussions with his religion, then getting closer to Allah. Quantitative research methods were used in this study. The sample consisted of 100 people consisting of 15 to 24 years with a convenience sampling technique. The data that has been analyzed found that there is no difference in Spiritual Well Being among Youth participating in Islamic lecture both online and offline